Scrutinization of marangoni convective flow of dusty hybrid nanofluid with gyrotactic microorganisms and thermophoretic particle deposition - Abbas, Munawar; Khan, Nargis; Hashmi, M. S.; İnç, Mustafa (Springer, 2024)
The objective of the present work is to study the influence of heat source on steady MHD Marangoni convective flow of incompressible hybrid nanofluid with deferment of dust particles over a sheet. The thermophoretic particle deposition, gyrotactic microorganisms, are taken into account along with heat source (temperature and exponential dependent) and mixed convection. The main goal of this study is to determine the thermal mobility of nanoparticles with water base fluid. The elements of Al2O3 and Cu are adept for the thermal analysis. We combined dust with microorganisms in this work to promote the heat and mass transport phenomena. It is vital for improving cooling systems in electronics, enhancing industrial heat transfer, and optimizing microfluidic devices. Additionally, the research aids environmental science by understanding pollutant dispersion and removal. It also finds applications in biomedical research, supporting drug delivery systems and medical diagnostics. Overall, this study promises advancements in technology, environmental conservation, and healthcare. The PDEs, which result from the conservation of concentration, energy, momentum and density of microorganisms in both hybrid nanofluid and dusty phases. Appropriate similarity transformations have been used to obtain the ODEs (ordinary differential equations). The resulting problem is numerically solved by a shooting technique based on the RKF-45th order. The results showed that the velocity profiles of the dust and fluid phases rise as the Marangoni convection parameter increases, but the microorganisms, concentration, and temperature profiles deteriorate in both phases.
Keywords: Marangoni convection; Gyrotactic microorganisms; Themophoretic particle deposition; Hybrid nanofluid; Heat source